URGENSI INTEGRASI TASAMUH DAN TA’AYUSH DALAM MENGIKIS KEPANATIKAN MAZHAB TEOLOGI: Tinjauan Qs. Ali ‘Imran Ayat 103 - Marfuah, Siti; Sassi, Komarudin (Muta'allim: Jurnal Pendidikan Agama Islam, 2025)
This study discusses the urgency of integrating the concepts of tasamuh (tolerance) and ta'ayush (harmonious coexistence) as a strategic effort to erode the fanaticism of theological schools of thought that often causes division among Muslims. By using a thematic interpretation approach to QS. Ali 'Imran verse 103, this study examines the values ​​of unity, oneness, and mutual respect contained in the verse as a normative basis for building an inclusive and harmonious attitude between schools of thought. The research method used is qualitative with analysis of the text of the Qur'an and related literature that supports the understanding of tasamuh and ta'ayush in the context of Islamic theology. The results of the study indicate that the integration of the two concepts is very important to reduce excessive fanaticism and strengthen Islamic brotherhood. This study recommends that scholars, educators, and community leaders prioritize the values ​​of tasamuh and ta'ayush in preaching and religious education in order to create a more inclusive, peaceful, and united Islamic society. Thus, this study makes an important contribution to the development of moderate and tolerant Islamic thought.Abstrak Penelitian ini membahas urgensi integrasi konsep tasamuh (toleransi) dan ta’ayush (hidup berdampingan secara harmonis) sebagai upaya strategis dalam mengikis sikap kepanatikkan mazhab teologi yang kerap menimbulkan perpecahan di kalangan umat Islam. Dengan menggunakan pendekatan tafsir tematik terhadap QS. Ali ‘Imran ayat 103, penelitian ini mengkaji nilai-nilai persatuan, kesatuan, dan saling menghormati yang terkandung dalam ayat tersebut sebagai landasan normatif untuk membangun sikap inklusif dan harmonis antarmazhab. Metode penelitian yang digunakan adalah kualitatif dengan analisis teks Al-Qur’an dan literatur terkait yang mendukung pemahaman tasamuh dan ta’ayush dalam konteks teologi Islam. Hasil penelitian menunjukkan bahwa integrasi kedua konsep tersebut sangat penting untuk mengurangi sikap fanatisme yang berlebihan dan memperkuat ukhuwah Islamiyah. Penelitian ini merekomendasikan agar para ulama, pendidik, dan pemimpin umat mengedepankan nilai-nilai tasamuh dan ta’ayush dalam dakwah dan pendidikan keagamaan guna menciptakan masyarakat Islam yang lebih inklusif, damai, dan bersatu. Dengan demikian, penelitian ini memberikan kontribusi penting dalam pengembangan pemikiran keislaman yang moderat dan toleran.